INTEGRATED MODEL OF TOURIST DESTINATION’S CAPACITY FOR TOURISM BUSINESS GOVERNANCE USING LITTLE’S LAW FORMULA IN SURABAYA CITY - Arif Fatchurahman; Rizky Amalia Sinulingga (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Tourism development is a strategic driver for enhancing local economies. Managing destination capacity has become essential for ensuring sustainability and high-quality visitor experiences. Surabaya, as a prominent tourism city, can benefit from improved efficiency and reduced operational costs through better capacity management. This study aims to develop an integrated destination capacity model in Surabaya by leveraging Lean Supply Chain principles and Little's Law. The goal is to identify and reduce waste in visitor flow while boosting operational efficiency. The study involves collecting data on visitor arrivals and their duration at Surabaya's tourist destinations. This data is analyzed using Little's Law (L = λW) to determine the optimal capacity that enhances visitor experience and minimizes waiting times and operational costs. Results indicate that implementing this integrated model significantly reduces visitor waiting times and enhances satisfaction. It also provides an effective strategy for managing visitor numbers during peak seasons, ensuring a more balanced flow of tourists. The model offers valuable insights for destination managers in efficiently allocating resources and managing capacity, especially in high-potential tourism cities like Surabaya. This approach not only enhances the visitor experience but also contributes to sustainable tourism management by balancing demand and operational efficiency.